Hubungan Antara Dukungan Keluarga Dengan Kelengkapan Imunisasi Dasar Pada Bayi Usia 9-11 Bulan Di Klinik Aminah Amin Tahun 2018 - Fitriana, Fitriana; Partijah, Suci; Pramardika, Dhito Dwi (Bunda Edu-Midwifery Journal (BEMJ), 2020)
Background: Immunization is a way to prevent infections caused by viruses or bacteria. Family support considers it important to administer immunizations to infants. The purpose of this study is to determine the relationship of family support to the completeness of immunization in infants aged 9-11 months at the Aminah Amin Clinic. The population increased by 42 parents with a sample of 21 parents who had babies aged 9-11 months. Samples were taken by accidental sampling technique. Variables that require family assistance and completeness of immunization. Descriptive analytics. Measuring instruments consist of a questionnaire for family support variables and KMS for Immunization Completeness variables. Data analysis used univariate and bivariate analyzes using the Chi-Squar statistical test. Results: Based on the results of statistical calculations, there is a relationship between family support and completeness of immunization in infants aged 9-11 months. Conclusion: There is a relationship between family support and completeness of immunization in infants aged 9-11 months in aminah amen clinic. Researchers hope to support all parties to help the success of a complete basic immunization program